Um estudo de caso sobre formação militar e sua relação com o desenvolvimento de habilidades socioemocionais no aluno - Pereira, Katia Cristiane Vomero (2015)
The work aimed to reflect issues related to the development of social and emotional skills in a group of young scholars and the importance of this knowledge as an aid to their healthy growth. The scenario of a practical activity carried out within a military training course served as field of study to this research, and tried to cover concepts such as self-awareness, motivation, overcoming limits, coping strategies, emotional control, empathy. In military training, while educational activity, the expansion of intelligence is essential for the full constitution of the individual. Such training grants, indirectly through behavior change, a chance for the improvement of inter and intrapersonal skills. Making a cut, the objective of the research was to investigate a specific instruction called Campaign Activity can be thought or not as supportive environment for the promotion of skills and / or social and emotional skills of the target audience. The research method used was the quantitative approach. A sample was selected from 160 (one hundred and sixty) young scholars of engineering degree and 25 (twenty five) educational agents (military instructors involved in the training process). The sample subjects answered questionnaires, which were analyzed expectations pre and post-campaign activity, the goals expected by forming agents (instructors) and real learning in terms of socio-emotional aspects by trainees. The results showed that the Campaign Activity can be thought of like a supportive environment for the student staff's social growth experiences. With different levels of development of social and emotional attributes by young people, the hypothesis could be confirmed that there is rather an opening that should be considered, to work with the student's individual powers on the emotional and social context